Application of Naïve Bayes Classifier Algorithm for Classification of Scholarship Recipients at SMA PGRI 2 Bandung - Jayadi, Jayadi; Raharja, Agung Rachmat; Pramudianto, Angga; Muchsam, Yoki (Trigin Publisher, 2024)
Education is one of the rights that each Indonesian citizen has. In this manner, there's a require for government consideration to assist underprivileged individuals in instruction, to be specific through grants. SMA II PGRI is one of the schools that organizes an underprivileged grant program, the grant is within the frame of educational cost waiver help. In its execution, officers regularly have trouble in deciding understudies who get grants based on foreordained criteria. In this way, it is fundamental to analyze information mining procedures utilizing naïve bayes classifiers in information preparing and is anticipated to be utilized to analyze grant grants for grant candidates. In this way it is fundamental to analyze information mining procedures utilizing naïve bayes classifiers in information handling and is anticipated to be utilized to analyze grants for grant candidates. Grant candidate information is carried out a information cleaning and decrease prepare so that the information is less but enlightening, so that it is appropriate for assist handling. At that point classification is done with Naïve Bayes classifier to deliver a classification likelihood demonstrate. The test brought about in an precision of 87.39% and was included within the great classification criteria.